TLR agonists as vaccine adjuvants in the prevention of viral infections: an overview - Kayesh, Mohammad Enamul Hoque; Kohara, Michinori; Tsukiyama-Kohara, Kyoko (Frontiers in Microbiology, 2023)
Tol-like receptor (TLR) agonists, as potent adjuvants, have gained attention in vaccine research for their ability to enhance immune responses. This study focuses on their application in improving vaccine efficacy against key viral infections, including hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV), SARS-CoV-2, influenza virus, and flavivirus (West Nile virus, dengue virus, and chikungunya virus). Vaccines are crucial in preventing microbial infections, including viruses, and adjuvants play a vital role in modulating immune responses. However, there are still many diseases for which effective vaccines are lacking or have limited immune response, posing significant threats to human health. The use of TLR agonists as adjuvants in viral vaccine formulations holds promise in improving vaccine effectiveness. By tailoring adjuvants to specific pathogens, such as HBV, HCV, HIV, SARS-CoV-2, influenza virus, and flavivirus, protective immunity against chronic and emerging infectious disease can be elicited.